Pelatihan Kapasitas Manajerial Petani Sereh Merah melalui Pembukuan Kas dan Evaluasi Kelayakan Usahatani di AMKE Oro-Oro Ombo, Batu Jawa Timur - Tirta Yoga; Nur Ida Iriani; Zuhdi Ma’sum; Agnes Quartina Pudjiastuti; Apria Fransiska; Grogorius Ceme (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to strengthen the managerial capacity of red lemongrass farmers in AMKE Oro-Oro Ombo, Batu, East Java, through training on cash bookkeeping, income analysis, and farming feasibility evaluation. The main problems faced by farmers are limited knowledge of financial management, lack of systematic bookkeeping, and inability to evaluate the profitability of their businesses, which often results in inaccurate decision-making and low competitiveness. The method applied included participatory training, mentoring, and simulation of financial records and feasibility analysis. The results of the program demonstrate that participants gained a better understanding of the importance of structured financial recording. Farmers who previously relied only on sales revenue calculations without considering fixed and variable costs are now able to prepare cash books, identify expenses, and evaluate profit margins accurately. Cash bookkeeping has proven to improve financial transparency and accountability, while income analysis has equipped farmers with the skills to assess their business sustainability. The feasibility evaluation, using indicators such as R/C and B/C ratios, showed that red lemongrass farming is profitable but still requires efficiency improvements to increase long-term sustainability. Overall, this training has enhanced farmers’ managerial skills, encouraged independent decision-making, and strengthened their capacity to face price fluctuations and market competition. The program is expected to support the continuity and competitiveness of red lemongrass agribusiness in AMKE Oro-Oro Ombo